Forming the Professional Identity of Future Teachers through Service-Learning - I. A. Rudneva; O. A. Kozyreva (Высшее образование в России)
In this article, the reference to the phenomenon of the professional identity of future teachers is caused, firstly, by the need to update meanings that are subject to permanent changes in the social reality surrounding a person, and secondly, by the importance of this personal education for high results of professional and pedagogical activities. The problem of forming the professional identity of future teachers through service-learning has become the subject of a special pedagogical study for the first time. The purpose of the article is to present the results of the study on the possibilities of service-learning as means of forming the professional identity of future teachers at the stage of professional training.The study focuses on the analysis of the results of testing service learning as innovative means of professional training of future teachers at a pedagogical university, aimed at forming their professional identity. The classical pedagogical experiment included diagnostic, formative and control stages (N=216). Diagnostics was carried out using the identity stage scale by J. Cote, the identity styles questionnaire by M. Berzonsky, the general self-efficacy scale by R. Schwarzer & M. Jerusalem. The statistical qualification of the results was performed using the Pearson χ2 goodness-of-fit criterion.The case of the Volgograd State Social-Pedagogical University demonstrated that service learning is used as an effective means of forming the professional identity of future teachers: a) the emotional component of professional identity (involvement, interest, focus on solving socially significant problems); b) the communication component of the professional identity (enrichment of the experience of interpersonal communication and interaction with different gender, age and social groups); c) the activity – based component of the professional identity (development of technological skills and creativity).The results of the study can be applied to the development of the problem of the professional identity of future teachers, the study of the possibilities of service-learning as a pedagogical method; they contribute to the theory and practice of continuous pedagogical education.